PENGARUH KUAT ARUS TERHADAP KEKERASAN, STRUKTUR MIKRO DAN LAJU KOROSI LAPISAN CHROMATE COATING PADA LOGAM ALUMINIUM - , BAMBANG HARI PRIYAMBODO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this reseach is to find out the effect of currents to the process of chromate coating on microstructure, hardness and corrosion rate of aluminium (Al). Aluminium was coated with copper (Cu), nickel (Ni) and chromium (Cr) variated by current (60 A, 90 A, and 120 A). Corrosion rate was tested using three-electrode cell method with 0.3% NaCl solution. Micro Vickers indentation was used for measuring surface hardness using load of 10 grams. An optical microscope was used to observe cross-sectional microstructure. The highest value of surface hardness and the lowest corrosion rate are obtained on specimens of Al/Cu/Ni/Cr by the current 90 A. Increasing current can improve corrosion resistance and surface hardness of the specimen. However, the optimum currents is 90 A, but when currents is increased again it increased the corrosion rate and decreased the surface hardness of the specimen. From microstructure observation of the cross-section of specimen show thin layer on the specimen surface. This layer increase the corrosion resistance and the surface hardness of the specimen.